2012
DOI: 10.3390/s121012988
|View full text |Cite
|
Sign up to set email alerts
|

Development of an RTK-GPS Positioning Application with an Improved Position Error Model for Smartphones

Abstract: This study developed a smartphone application that provides wireless communication, NRTIP client, and RTK processing features, and which can simplify the Network RTK-GPS system while reducing the required cost. A determination method for an error model in Network RTK measurements was proposed, considering both random and autocorrelation errors, to accurately calculate the coordinates measured by the application using state estimation filters. The performance evaluation of the developed application showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Results of network RTK positioning from other research [23] has indicated a horizontal positioning accuracy of ±5 cm in Southern Germany. [6,12,24] demonstrated positioning errors of ±2.0 cm and ±5.0 cm for the horizontal and height coordinates, respectively, using network RTK. It follows that the NTRIP client in the app can carry out 3-D positioning using network RTK technology easily and in real-time using the GNSS receiver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of network RTK positioning from other research [23] has indicated a horizontal positioning accuracy of ±5 cm in Southern Germany. [6,12,24] demonstrated positioning errors of ±2.0 cm and ±5.0 cm for the horizontal and height coordinates, respectively, using network RTK. It follows that the NTRIP client in the app can carry out 3-D positioning using network RTK technology easily and in real-time using the GNSS receiver.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [5] evaluated the possibility of adopting a smartphone-based monitoring system for coastal monitoring through prevision evaluation using smartphone-based technology. In [6] an app making it possible to position network RTK using a smartphone was implemented. Educational content has been produced and distributed for plastic surgery trainees and surgeons with smartphones [79].…”
Section: Introductionmentioning
confidence: 99%
“…The idea is to provide the cyclist with some wearable gadgets embedded in his/her clothes (in the gloves or the helmet) that, thanks to a personal area network communication interface, can obtain information from the V-Alert application and alert the cyclist about closing vehicles via some LEDs, sounds, or vibration systems available to the rider depending on the smartphone. Also, the positioning error of the GPS (~5 m) must be fixed, so in future steps position accuracy must be improved by including a Differential GPS system or application [19]. Moreover, we are improving the mobile application algorithm in order to discard the information of those vehicles that will not intersect with the cyclist and are not a risk for him/her.…”
Section: Discussionmentioning
confidence: 99%
“…developed a Network RTK (NRTK) GPS smartphone application with less than 1 cm horizontal accuracy, less than 3 cm vertical accuracy and 0.71 sec latency times [79].…”
Section: Accuracy Of Smartphone Localizationmentioning
confidence: 99%